IMPLEMENTATION OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE MOTIVATION AND WORK PERFORMANCE AT PT AFLAH NUSANTARA INDONESIA - Sirojul Munir; Ria Khoirunnisa'; Muhammad Fadlullah Ali (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study is designed to examine the impact of transformational leadership implementation on employee motivation and work performance at PT Aflah Nusantara Indonesia. A quantitative survey-based method was applied involving 150 employee participants selected through a simple random sampling technique. The data collection instrument consisted of structured questionnaires using a five-point Likert scale, while data analysis employed multiple linear regression using SPSS version 26. Research findings indicate that transformational leadership has a significantly positive influence on employee performance, with a regression coefficient of 0.421 and a significance value of 0.000. Work motivation also demonstrates a significantly positive effect on performance, with a regression coefficient of 0.687 and a significance value of 0.000. Simultaneously, transformational leadership and work motivation significantly affect work performance, with an F-value of 87.452 and a coefficient of determination of 54.2 percent. This research reinforces the urgency of strengthening transformational leadership capabilities and enhancing work motivation as strategic approaches to optimizing employee performance within business entities.